The role of disease duration and severity on novel clinical subtypes of Parkinson disease. (April 2020) - Erro, Roberto; Picillo, Marina; Scannapieco, Sara; Cuoco, Sofia; Pellecchia, Maria Teresa; Barone, Paolo
Abstract: Introduction: One of the latest subtyping systems of Parkinson disease (PD) identifies motor severity, cognitive dysfunction, dysautonomia, and rapid eye movement behavior disorder as key features for phenotyping patients into three different subtypes (i.e., mild motor-predominant, diffuse-malignant and intermediate). Since PD subtypes are clinically most relevant if they are mutually exclusive and consistent over-time, we explored the impact of disease stage and duration on these novel subtypes. Methods: One-hundred-twenty-two consecutive patients, with a disease duration ranging from 0 to 20 years, were allocated as suggested into these three subtypes. The relationship between either disease duration or stage, as measured by the Hoehn and Yahr staging, and subtype allocation was explored. Results: Significant differences in subtype distribution were observed across patients stratified according to either disease duration or staging, with the diffuse-malignant subtypes increasing in prevalence as the disease advanced. Both disease duration and staging were independent predictors of subtype allocation. Conclusions: These novel PD subtypes are significantly influenced by disease duration and staging, which might suggest that they do not represent mutually exclusive disease pathways. This should be taken into account when attempting correlations with putative biomarkers of disease progression. Highlights: Identification of Parkinson Disease subtypes has been deemed as a research priority in the field. A novel subtyping system has been proposed based on four clinical features including motor disability, cognitive and autonomic dysfunction, and rapid eye movement behavior disorder. The relationship between these novel subtypes and disease duration and staging is unknown. There is a significant influence of both disease duration and staging on these subtypes.